To Claudio Guillén. In Memoriam (XXI Century. Spanish Literature and Culture, 2007)
Words on the occasion of the death of Claudius Guillén, whose work developed preferably in the areas of comparative literatureand of the theory of literature, has left an important mark on the thinking of our days with fundamental contributions in the definition of concepts such as "literary history", "genres", "movements", "periods", "schools".
Keywords: Claudio Guillén; In memoriam; 21 Century